2021
DOI: 10.1016/j.chest.2021.02.062
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Function and Radiologic Features in Survivors of Critical COVID-19

Abstract: Background More than 20% of hospitalized patients with coronavirus disease 2019 (COVID-19) develop acute respiratory distress syndrome (ARDS) requiring intensive care unit (ICU) admission. The long-term respiratory sequelae in ICU survivors remain unclear. Research question what are the major long-term pulmonary sequelae in critical COVID-19 survivors? Study Design and Methods Consecutive patients with COVID-19 requiring ICU admission were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
156
2
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(215 citation statements)
references
References 51 publications
(63 reference statements)
21
156
2
8
Order By: Relevance
“…We found that the most common abnormal CT patterns were bilateral lung involvement, subpleural reticular, ground-glass opacity density with a peripheral location, which agrees with the previous results 8,10,25,32 . Our study revealed a signi cant robust positive single correlation between the abnormal CT ndings and male sex, age > 59 years, ex-smoker, and abnormal radiography, as well as multiple correlations, except for ex-smoker.…”
Section: Discussionsupporting
confidence: 92%
“…We found that the most common abnormal CT patterns were bilateral lung involvement, subpleural reticular, ground-glass opacity density with a peripheral location, which agrees with the previous results 8,10,25,32 . Our study revealed a signi cant robust positive single correlation between the abnormal CT ndings and male sex, age > 59 years, ex-smoker, and abnormal radiography, as well as multiple correlations, except for ex-smoker.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the few series that have been published regarding functional alterations detected three-to-four months after a COVID-19 pneumonic episode mainly examined the DL CO [1][2][3][4][5][6][7][8][9][10]. As shown in the table summarising these studies (Table 7), and despite the fact that there is little variation in the percentage over the reference value of DL CO , when the alteration was defined by a decrease under 80% in the theoretical percentage (51-57%), except for series that include only post-ICU patients [10]; however, when this was measured as a decrease below the LLN, DL CO alteration ranged from 17% in our work to 24% as reported by Lerum et al [1], and 34% in another study nine weeks after discharge [32]. In other studies, the relationship between predictor variables and lung involvement was enhanced by different linear correlation analyses without defining specific cut-off points for the definition of DL CO alteration [6,8].…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a limited number of studies have been published that analysed the clinical and functional alterations of patients hospitalised for SARS-COV-2 pneumonia, 3-4 months after their hospital discharge [1][2][3][4][5][6][7][8][9][10]. In these cases of severe COVID-19 pneumonia, the most frequently described alterations are a decrease in forced vital capacity (FVC), carbon monoxide transfer capacity (DL CO ), total lung capacity, and reduction in the 6-min walk test (6MWT) [1][2][3][4][5][6][7][8][9][10]. However, the results described in these studies are not homogeneous.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence at hospital discharge shows that nearly half of survivors of COVID-19 have impaired lung diffusing capacity for carbon monoxide, a quarter have reduced total lung capacity, and this is correlated with the severity of disease [ 20 ]. Furthermore, 55% to 80% of COVID-19 patients show impaired pulmonary function and radiologic abnormalities three months after ICU discharge, while 21% show fibrotic patterns at the computed tomography (CT) [ 17 , 21 , 22 ]. It is still unclear whether patients will show recovery over time or irreversible fibrosis will develop.…”
Section: Discussionmentioning
confidence: 99%